Tanggung Jawab Hukum Pengelola dalam Menjamin Keamanan dan Keselamatan Wisatawan di Kawasan Wisata Geopark Sukabumi - Novitasari, Fitri; Nuraeny, Henny; Mulyadi, Mulyadi (AHKAM, 2025)
Geopark tourism areas possess significant natural potential while also presenting considerable risks, such as natural disasters and visitor accidents, which demand optimal safety and security systems from management authorities. This study aims to analyze the responsibility of PT Geopark Sukabumi in ensuring the safety and security of the tourist areas it manages. Using a qualitative approach with a case study method, data were collected through in-depth interviews, field observations, and analysis of regulatory and policy documents. The findings reveal the absence of a systematic risk management system, limited transparency in incident reporting, and weak oversight from local government authorities, which collectively increase the likelihood of serious incidents, legal risks, and damage to the geopark’s image as a sustainable tourism destination. These results indicate that current safety management practices in the area do not meet adequate standards. The study concludes that the management must implement a standardized safety management system, enhance human resource capacity, strengthen transparency in reporting, and encourage active involvement of local governments in supervision. The implications of this research are critical for formulating tourism policies focused on safety and consumer protection, particularly in conservation-based tourist areas prone to natural hazards.